Marine and Non-marine Jurassic: Boundary Events and Correlation - Sha, Jingent (2006)
A variety of experiences and approaches have been accumulated which resulted in the availability of highly precise correlation within the marine Jurassic, though correlation of marine Triassic/Juurassic, Jurassic/Cretaceous boundaries and particularly the non-marine international Jurassic correlation, have long been debated and not yet resolved on a global scale. Furthermore, our knowledge is still limited regarding the major geological events, as well as their record and potential correlation during the Jurassic. Non-marine formations should be correlated with marine formations as the international chronostratigraphical scale is based on marine strata. Therefore, the non-marine strata must be integrated into the chroronostratigraphic scheme by correlating non-marine with marine strata, mainly by means of the fossil content and other geological data, for example sequence stratigraphy. Recognition of depositional systems and subsystems and determination of their fluctuation in space and time lead to a high-resolution sequence stratigraphic analysis and internally consistent sequence stratigraphic scheme of marginalmarine and continental deposits. This template can be compared with fossiliferous marine sediments. Sedimentation in the shallow, epeiric basins is particularly sensitive to reflect changes in sea level. Correlative significance is of transgressive surfaces and it is enhanced when they are coupled with their non-marine correlative surfaces. Development of transgression and recognition of its coeval effects in continental deposits is of crucial significance in reliable sequence stratigraphic correlation between fossiliferous marine and non-marine deposits.